Electrophysiologic similarities of overdose between digoxin and bufadienolides found in a Chinese aphrodisiac - Maxwell Bressman (Journal of Arrhythmia, 2017)
Classically derived from toad venom, bufadienolides are a group of cardioactive steroids with properties similar to digoxin. Some traditional Chinese medications, including several aphrodisiacs, contain bufadienolides. Owing to their physiologic similarities to digoxin, bufadienolides have been shown to produce a toxic profile similar to that of digoxin and there have been multiple case reports of the use of these aphrodisiacs resulting in death. This report will describe a case that illustrates the electrophysiologic similarities between bufadienolide toxicity and digoxin toxicity as well as the treatment of bufadienolide toxicity.